Алгоритм контроля и оценивания частично правильных ответов в ходе дистанционного тестирования знаний - Штангей, С. В. (УАДО, 2004)
Questions of the control of knowledge trained which is carried out during remote education are considered. The approach to standardization of types of test tasks and ways of the control of answers trained is offered. The mathematical model of estimation in part right answers trained is offered. The generalized algorithm of the control in part right answers trained is developed.
Keywords: дистанционное тестирование знаний; оценивание правильных ответов